Gyrodactylus molweni sp. n. (Monogenea: Gyrodactylidae) from Chelon richardsonii (Smith, 1846) (Mugilidae) from Table Bay, South Africa. (August 2021) - Christison, Kevin W.; Vaughan, David B.; Shinn, Andrew P.; Hansen, Haakon
Abstract: Gyrodactylus molweni sp. n. is described from the body surface and fins of the South African mullet, Chelon richardsonii (Smith, 1846) collected from Table Bay Harbour, Cape Town and is compared to five other Gyrodactylus species described from grey mullets globally namely G. zhukovi Ling, 1963 and G. mugili Zhukov, 1970 from Planiliza haematocheila (Temminck and Schlegel, 1845); G. mugelus Rawson, 1973 from Mugil cephalus L. ; G. curemae Conroy and Conroy, 1985 from Mugil curema Valenciennes, 1836 and G. xiamenensis Zang, Yang and Liu, 2001 from Planiliza macrolepis (Smith, 1846). Morphologically, G. molweni sp. n. has prominent ventral bar processes that near cover the hamulus roots, marginal sickles with large rhomboid heels, slender shafts and fine points that extend beyond the sickle toes. Gyrodactylus molweni sp. n. can, however, be readily differentiated: G. mugili and G. xiamenensis have ventral bars with small ventral processes; G. zhukovi has marginal hooks sickles with slender shafts and proportionately short points and open-faced blades; G. mugelus possesses marginal hook sickles with deep, rounded heels, forward slanting shafts and an angular, square line to the inner face of the blades. Although the length of the marginal hooks of G. curemae are similar to G. molweni sp. n., their hamuli are double the size. A GenBank BlastN search with the 931 bp sequence covering ITS1, 5.8S and ITS2 gave no close hits; the nearest species for which sequences are available is G. nipponensis Ogawa and Egusa, 1978 (identity 96.56%, 899/931 bp). The proposal of G. molweni sp. n. as a new species, therefore, is well supported by both the molecular and morphological analyses presented herein. This Gyrodactylus species is the first to be described from C. richardsonii and only the second Gyrodactylus species to be described from the marine environment off the African continent. Graphical abstract: Image 1 Highlights: Gyrodactylus molweni sp. n is described from the body surface and fins of the South African mullet, Chelon richardsonii (Smith, 1846) collected from Table Bay Harbour, Cape Town. The description of Gyrodactylus molweni sp. represents only the second Gyrodactylus species to be described from the Marine environment off the African continent.